2013
DOI: 10.1089/sur.2012.096
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance of Surgical Site Infection after Cholecystectomy Using the Hospital in Europe Link for Infection Control through Surveillance Protocol

Abstract: Background: The third most common healthcare-associated infection is surgical site infection (SSI), accounting for 14%-16% of infections. These SSIs are associated with high morbidity, numerous deaths, and greater cost. Methods: A prospective study was conducted to assess the incidence of SSI in a single university hospital in Croatia. We used the Hospital in Europe Link for Infection Control through Surveillance (HELICS) protocol for surveillance. The SSIs were classified using the standard definition of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 19 publications
2
22
1
2
Order By: Relevance
“…This particular measure mainly prevents from postoperative pneumonia, so it does not influence the prevention of incisional SSI. Finally, as in parallel to other series reviewed (9,11,13), the microorganisms isolated in our study were the most often identified in such kind of surgical procedures, including Escherichia coli (47.8%), Klebsiella pneumoniae (13.1%) and Enterococcus faecium (13.1%).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…This particular measure mainly prevents from postoperative pneumonia, so it does not influence the prevention of incisional SSI. Finally, as in parallel to other series reviewed (9,11,13), the microorganisms isolated in our study were the most often identified in such kind of surgical procedures, including Escherichia coli (47.8%), Klebsiella pneumoniae (13.1%) and Enterococcus faecium (13.1%).…”
Section: Discussionsupporting
confidence: 76%
“…Antibiotic choice should be based on the spectrum of microorganisms most frequently involved in each surgical location, opting for the safer, cheaper and less likely to favor the emergence of drug-resistance bacteria. In order to ensure the effectiveness of antibiotic prophylaxis, its administration is usually protocolized, being not indicated in the case of a low risk gallbladder surgery (9). These interventions have an overall incidence of SSI of 1% to 3%, which range from 0.5% in laparoscopic to 6% in open surgery.…”
Section: Introductionmentioning
confidence: 99%
“…So, we can conclude that endoscopic surgeries are associated with low SSI in gallbladder surgeries as compared to the open gallbladder surgeries. [12627]…”
Section: Discussionmentioning
confidence: 99%
“…[1] There are evidence of postoperative morbidity due to SSI. So it is needed to improve the outcome of surgical procedures and hence advised to give antibiotic prophylaxis.…”
Section: Introductionmentioning
confidence: 99%
“…1 Bile may contain multiple aerobic as well as anaerobic bacteria thus increasing the risk of SSI. 2 Some newly developed guidelines do not support the use of prophylactic antibiotics in routine laparoscopic cholecystectomy (LC).…”
Section: Introductionmentioning
confidence: 99%